2005
DOI: 10.1300/j031v17n04_05
|View full text |Cite
|
Sign up to set email alerts
|

An International Review of the Long-Term Care Workforce

Abstract: The developed world's population is aging, due to trends of increased life expectancies and decreased fertility rates. These trends are predicted to increase demand on long-term care services. At the same time, the long-term care workforce is in shortage in most of the developed world. Moreover, such shortages are expected to increase due to parallel socio-demographic factors. The increase in demand for longterm care, coupled with shortage in supply of care workers, has promoted some attention from policymaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 12 publications
0
100
0
1
Order By: Relevance
“…The Institute of Medicine concluded that our country is facing an "impending health care crisis as the number of older patients with more complex health needs increasingly outpaces the number of health care providers with the knowledge and skills to adequately care for them" (Institute of Medicine, 2008, 1). Other developed countries experience similar shortages in long-term care staff (Hussein & Manthorpe, 2005). Given existing high turnover and vacancy rates, increased demand for these paraprofessionals will be hard to satisfy (Wiener, 2006;Decker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Medicine concluded that our country is facing an "impending health care crisis as the number of older patients with more complex health needs increasingly outpaces the number of health care providers with the knowledge and skills to adequately care for them" (Institute of Medicine, 2008, 1). Other developed countries experience similar shortages in long-term care staff (Hussein & Manthorpe, 2005). Given existing high turnover and vacancy rates, increased demand for these paraprofessionals will be hard to satisfy (Wiener, 2006;Decker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In common with other developed countries (Hussein and Manthorpe 2005), UK policy has recently emphasised the recruitment and retention of staff in the social care of frail older people (DH 2001). In A Quality Strategy for Social Care, the importance of the workforce was reiterated : 'Social care staff comprise the greatest asset services possess ' (DH 2000: 9).…”
Section: The Workforcementioning
confidence: 99%
“…Acceptance of traditional gender roles may curtail women's freedom of movement, and their autonomy as employees. While shortages in the social work and related workforces mean that migrant workers are of growing importance to all social work and associated employers (Hussein and Manthorpe, 2005), the data reported above suggest that if employers provide as much flexibility as they can for female employees to manage the demands of family and childcare and of work this may lead to greater retention or satisfaction. Workplace support for women who may have to take leave for family duties, or who need childcare, may be attractive to migrant female workforces.…”
Section: Employers and Human Resources Issuesmentioning
confidence: 99%